The final particles of wenyan (based on the novel of pu songling «miss ying-ning, or the laughing girl»). - Nurzhayeva., A. M. (Journal of Oriental Studies, 2016)
The article is devoted to the final particles, which used to replace the punctuation in classical Chinese. The study carried out on novel «Miss Ying-Ning, or The laughing girl» of Chinese writer Pu Sunlin into the appropriate languages.